T cells, NK cells, and tumor-associated macrophages in cancer immunotherapy and the current state of the art of drug delivery systems - Yang, Ya-long; Yang, Fei; Huang, Zhuan-qing; Li, Yuan-yuan; Shi, Hao-yuan; Sun, Qi; Ma, Yue; Wang, Yao; Zhang, Ying; Yang, Sen; Zhao, Guan-ren; Xu, Feng-hua (Frontiers in Immunology, 2023)
The immune system provides full protection for the body by specifically identifying ‘self’ and removing ‘others’; thus protecting the body from diseases. The immune system includes innate immunity and adaptive immunity, which jointly coordinate the antitumor immune response. T cells, natural killer (NK) cells and tumor-associated macrophages (TAMs) are the main tumor-killing immune cells active in three antitumor immune cycle. Cancer immunotherapy focusses on activating and strengthening immune response or eliminating suppression from tumor cells in each step of the cancer-immunity cycle; thus, it strengthens the body’s immunity against tumors. In this review, the antitumor immune cycles of T cells, natural killer (NK) cells and tumor-associated macrophages (TAMs) are discussed. Co-stimulatory and co-inhibitory molecules in the three activity cycles and the development of drugs and delivery systems targeting these molecules are emphasized, and the current state of the art of drug delivery systems for cancer immunotherapy are summarized.